2022
DOI: 10.1001/jamanetworkopen.2022.0625
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tranexamic Acid Administration With Mortality and Thromboembolic Events in Patients With Traumatic Injury

Abstract: IMPORTANCETranexamic acid is widely available and used off-label in patients with bleeding traumatic injury, although the literature does not consistently agree on its efficacy and safety. OBJECTIVE To examine the association of tranexamic acid administration with mortality and thromboembolic events compared with no treatment or with placebo in patients with traumatic injury in the literature. DATA SOURCES On March 23, 2021, PubMed, Embase, and the Cochrane Library were searched for eligible studies published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…Tranexamic acid (TXA) in particular has emerged as a useful therapeutic agent to promote hemostasis and to prevent blood loss in injured patients. Prior to its application to trauma, TXA was routinely used in orthopedic, obstetrics and gynecology, and cardiothoracic patients in hospital and surgical settings 5–7 . Most recently, in the Study of Tranexamic Acid During Air and Ground Prehospital Transport (STAAMP) Trial, prehospital TXA was associated with lower mortality in specific subgroups of injured trauma patients who received TXA close to the time of their injuries 3,8,9 .…”
mentioning
confidence: 99%
“…Tranexamic acid (TXA) in particular has emerged as a useful therapeutic agent to promote hemostasis and to prevent blood loss in injured patients. Prior to its application to trauma, TXA was routinely used in orthopedic, obstetrics and gynecology, and cardiothoracic patients in hospital and surgical settings 5–7 . Most recently, in the Study of Tranexamic Acid During Air and Ground Prehospital Transport (STAAMP) Trial, prehospital TXA was associated with lower mortality in specific subgroups of injured trauma patients who received TXA close to the time of their injuries 3,8,9 .…”
mentioning
confidence: 99%
“…[39] Although it may help reduce surgical blood loss, administering TXA to unsuitable patients or at inappropriate doses may increase the risk of thrombosis. [40][41][42][43] However, most studies have reported that TXA use before and during lumbar fusion surgery does not increase the risk of postoperative thrombosis. Surgeons should be cautious when identifying patients at a high risk of thrombosis before using TXA.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, many orthopaedic surgery patients with notable comorbidities do not receive perioperative TXA even though they might derive the most benefit from its use. Evidence supporting the concern that TXA may lead to a higher risk of pulmonary embolism can only be found in studies of complex trauma patients receiving high doses of the drug (2 to 4 g intravenously) 2,3 . This concern is not supported in the orthopaedic literature.…”
Section: Commentarymentioning
confidence: 99%